Modern Pastoralism and the Middle Landscape - Peter G. Rowe (Oz, 1989)
According to commonplace definitions, a myth is a story that expresses and symbolizes deep-seated and exemplary aspects of human existence. Moreover, it often sets out to resolve conflict or to allow reconciliation of two otherwise antithetical positions...